HISTOPATHOLOGICAL EXAMINATIONS PROFILE OF BLADDER DISEASES IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL FROM JANUARY 2015 TO DECEMBER 2019 - Krismaningrum, Veronika Intan; Rahaju, Anny Setijo; Herawati, Lilik; Soetojo (Indonesian Urological Association, 2022)
Objective: This study aimed to analyze the profile of bladder disease in Soetomo General Hospital based on histopathological examination. Material & Methods: This study was using secondary data. Histopathological examination data of patients with bladder disease were evaluated based on age, gender, and histopathological types. Results: There were 419 patients with bladder abnormalities. Non-neoplasm bladder diseases were found in 62 patients consisted of 56 patients (90.32%) with cystitis and 6 patients (9.67%) with glandular cystitis. Neoplastic bladder diseases were found in 357 patients and were divided into benign and malignant neoplasm. Benign neoplasms were found in 11 patients consisted of 5 patients (45.45%) with UP and 6 patients (54.54%) with IUP. Malignant neoplasms were found in 340 patients consisted of 300 patients (88.23%) with urothelial carcinoma, 26 patients (7.64%) with adenocarcinoma, 14 patients (4.12%) with SCC. Moreover, six male patients with PUNLMP were also reported. Conclusion: Histopathological examination in patients with bladder abnormalities shows that neoplastic bladder diseases (357/419, 85.20%) were more common than non-neoplastic bladder disease (62/419, 14.80%).